2009
DOI: 10.1530/eje-09-0170
|View full text |Cite
|
Sign up to set email alerts
|

Improving glucocorticoid replacement therapy using a novel modified-release hydrocortisone tablet: a pharmacokinetic study

Abstract: Background: Endogenous plasma cortisol levels have a well-defined circadian rhythm. The aim of this project is to develop a once daily oral dual-release formulation for cortisol replacement therapy that mimics the diurnal variation in the plasma cortisol profile. Objective: To determine single-dose plasma pharmacokinetics and dose-proportionality of oral 5 and 20 mg dual-release hydrocortisone tablets in healthy volunteers. In addition, the effect of food intake was investigated for the 20 mg dose. Design: A r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
111
1
6

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(125 citation statements)
references
References 53 publications
7
111
1
6
Order By: Relevance
“…In particular, a dual-release preparation of hydrocortisone (Plenadren) was developed to maintain cortisol levels in a more physiological range, as clearly demonstrated in a phase I study [21].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, a dual-release preparation of hydrocortisone (Plenadren) was developed to maintain cortisol levels in a more physiological range, as clearly demonstrated in a phase I study [21].…”
Section: Discussionmentioning
confidence: 99%
“…In a study to determine single dose pharmacokinetics and dose proportionality it was shown that the time to reach a serum concentration of cortisol (>200 nmol/l) of clinical significance was within 25 minutes and a peak of 400450 nmol/l was obtained within 50 minutes after the 20 mg tablet. Serum cortisol persisted above 200 nmol/l for around 6 h thereafter whereas all serum concentrations 1824 h after intake were below 50 nmol/l [Johannsson et al 2009]. This formulation was unable to fully replicate the physiological cortisol rhythm as taking the tablet at 07:00 misses the 03:00 cortisol rise.…”
Section: Circadian Hydrocortisone Infusionsmentioning
confidence: 99%
“…One reason for impaired subjective health may be that common replacement regimens are not able to mimic the physiological diurnal pattern of cortisol secretion (1). This might be overcome by promising new developments of time-released medication (17,18). In addition, subjective health may also be affected by multiple aspects of SAI such as the mere fact of having a chronic disease, the need for chronic medication, or working disability (7,19).…”
Section: Sai Patients (Nz18)mentioning
confidence: 99%